Memória e interdiscurso em: o Guardador de Águas de Manoel de Barros - Silvério, Nirce Aparecida Ferreira (2006)
This research aims at studying four poems from the book O guardador de águas, de Manoel de Barros, where through a methodology qualitative-interpretative, search for inter discursive relations and, for such, start from traces of discursive and historical memory. Theoretically, it´s based on the theoretical findings of the Analysis of the Speech of French line derived from the studies of Michel Pêcheux and Michel Foucault, among other authors. Fundamental concepts of this area of studies starting from the Foucaultian vision regarding the domain of memory, anticipation and actuality, that are re-elaborated by Courtine(1981), and, of the slight knowledge of techniques of coercions and correlated resistance enrolled by Gregolin(2004b).It´s described and analyzed meta enunciate reflections that constitute the corpus in question aiming at identifying characterizing of statements pre constructed amongst different discursive formations, considered as heterogeneous and of moving sense. The phrasal sense related to different discursive formation inside and outside the literary field will also be analyzed. Thus, the discursive materiality, under analysis, is understood as monument bringing in itself, the socio historical and cultural conditions that make possible its existence and functioning as speech and show characterizations of involved citizens in its constitution process. It´s still tried to be explained, the socio historical and cultural context that made possible the return of certain enunciates and the assumed senses, constituting inter discursive and historical relations.